A New Stability Indicating Liquid Chromatographic Method for the Quantification of Felodipine - Kallepalli, Pramadvara (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Felodipine is used for the treatment of hypertension. In the present study a new stability-indicating RP-HPLC method has been established for the determination of Felodipine.in pharmaceutical dosage forms and the method was validated. Material and Methods: Shimadzu Model CBM-20A/20 Alite, UFLC system was used for the assay of Felodipine using a mixture of phosphate buffer (pH 7.0) and acetonitrile (20:80, v/v) as mobile phase with a flow rate of 1.2 ml/min (UV detection at 234 nm). Forced degradation studies were performed by exposing Felodipine to different stress conditions and the method was validated as per ICH guidelines. Results and Discussion: Felodipine is found to be more sensitive towards oxidative degradation. Conclusion: The proposed method is simple and economical and can be used for the determination of Felodipine in pharmaceutical formulations.